Genomic analysis and clinical importance of Escherichia coli isolate from patients with sepsis - Arindam Chakraborty; Prabha Adhikari; Shalini Shenoy; Vishwas Saralaya (Wolters Kluwer Medknow Publications, 2015)
Context: Escherichia coli is a major cause of bloodstream infections and death due to sepsis. Bacteremic isolates harbor a significantly greater repertoire of virulence factors (VFs) in contrast with commensal E. coli isolates. Aims: The aim was to determine the relationships between E. coli VFs, phylogenetic groups, and their clinical importance. Settings and Design: This descriptive study was carried out in a multi-specialty tertiary care hospital. Materials and Methods: Escherichia coli isolates from consecutive episodes of bacteremia in 100 patients were screened for their VFs, phylogenetic group, and their effect on patient's clinical outcome. Virulence genes of all isolates were determined by multiplex polymerase chain reaction (PCR). Phylogenetic analysis was performed by triplex PCR methods. Estimation of risk of death was calculated using APACHE score II calculator. Results: Of the 100 patients, the most common predisposing factors were diabetes (42%), followed by carcinoma (23%). On analysis of the VF genes of the isolates, a majority of strains (88%) were possessing the fimH gene followed by iutA (76%), papC (44%), cnf1 (16%), hlyA (16%) and neuC (5%) respectively. Phylogenetic analysis revealed that 25 (25%) isolates belonged to phylogroup A, 8(8%) strains to group B1, 30 (30%) were from group B2 and 37 (37%) were from group D. The incidence of iutA gene was significant in higher APACHE II score group. Conclusions: Our findings indicate that virulent as well as commensal strains are capable of causing sepsis. Host related predisposing factors, adherence factors, and iron uptake are essential for the survival of the sepsis inducing strains.